Use of Polyphenols as Modulators of Food Allergies. From Chemistry to Biological Implications - Catarina Bessa; Telmo Francisco; Ricardo Dias; Nuno Mateus; Victor de Freitas; Rosa Pérez-Gregorio (Frontiers in Sustainable Food Systems, 2021)
The multifactorial process of aging predisposes humans to infections and inflammatory disorders, thus affecting their quality of life and longevity. Given this reality, the need to increase the consumption of bioactive compounds, like dietary polyphenols emerges in our daily basis mostly due to their health related effects in slowing-down the incidence of chronic and degenerative diseases and even food allergy, which has been growing rapidly in prevalence currently affecting 5% of adults and 8% of children. Polyphenols embrace a large family of secondary metabolites from plant-derived foods and food wastes and are considerable of interest since they have attracted special attention over the years because of their reported anti-inflammatory and antimicrobial properties along with their high antioxidant capacity. These compounds are claimed as nutraceuticals with protective effect in offsetting oxidant species over-genesis in normal cells, and with the potential ability to stop or reverse oxidative stress-related diseases. Plant-derived foods represent a substantive portion of human diet containing a significant amount of structurally diverse polyphenols. There is a need to understand the polyphenolic composition of plant-derived foods mainly because of its chemistry, which discloses the bioactivity of a plant extract. However, the lack of standardized methods for analysis and other difficulties associated to the nature and distribution of plant polyphenols leads to a high variability of available data. Furthermore, there is still a gap in the understanding of polyphenols bioavailability and pharmacokinetics, which clearly difficult the settlement of the intake needed to observe health outcomes. Many efforts have been made to provide highly sensitive and selective analytical methods for the extraction (liquid-liquid; solid-liquid; supercritical-fluid), separation (spectrophotometric methods) and structural identification (chromatographic techniques, NMR spectroscopy, MS spectrometry) of phenolic and polyphenolic compounds present in these extracts. Liquid chromatography coupled to mass spectrometry (LC-MS) has been a fundamental technique in this area of research, not only for the determination of this family of compounds in food matrices, but also for the characterization and identification of new polyphenols classified with nutraceutical interest. This review summarizes the nature, distribution and main sources of polyphenols, analytical methods from extraction to characterization to further evaluate the health effects toward immune reactions to food.